Architecture‐aware routability‐driven placer for large‐scale mixed‐size designs. Issue 8 (12th November 2019) - Datta, Prasun; Mukherjee, Shyamapada
Abstract : In this study, the authors have presented a simple but robust routability‐driven placement for the mixed‐size designs. The proposed technique is implemented through (i) look‐ahead legalisation‐based global placement, (ii) congestion removal and (iii) detailed placement stages. A balanced clustering technique has been proposed to group the circuit blocks into clusters based on the types of circuit blocks and their connectivity. A 0‐1 integer programming‐based global placement method is framed, which performs look‐ahead legalisation. A new site information table concept is introduced to keep the information about each placement cell. Based on the divide conquer strategy, placement area is divided into a region to reduce problem size. A force‐directed method has been conceived to select an appropriate region for global placement for the blocks of a cluster. A new congestion removal approach substitutes the legalisation stage to remove circuit block congestion and pin density in different regions. Finally, a gain‐based strategy has been introduced for routability‐driven detailed placement. The proposed technique is implemented and tested on ICCAD 2012 benchmark circuits. It achieves 1.92 and 0.13% improvements in terms of half perimeter wirelength and routing congestion w.r.t. recent placers.